Papyrusmaterial aus Elephantine und seine signifikanten Merkmale - Krutzsch, Myriam (Zeitschrift für ägyptische Sprache und Altertumskunde, 2020)
Decades of restorational processing of the writing surface, papyrus, have resulted in observations of detailed material structures that can vary depending on the production site. This paper presents characteristic traits of the papyrus material that comes from Elephantine manufactories. This material is clearly distinct from material from other places, for example Thebes, Illahun, and Tebtunis. The differences lie less in the various color nuances than in the papyruses’ general physical characteristics, fiber structure, and special surfaces. All visual observations and all simple measurements made so far have received support from natural-scientific investigations for quite some time now.